A comparison study between bailey bridge and prestressed concrete bridge / Kamarul Izwad Che Kamarudin - Che Kamarudin, Kamarul Izwad (2008)
This study was aimed to study about the Bailey bridge system and the reinforced concrete bridge in Malaysia. As we know, bridge is one of the road system or as a transportation medium for all people and vehicle. There are many bridge that construct based on many methods. But normally the bridge construction needs more times to construct. So, there have a problem for those who want to use the bridge immediately. So, we have a new technology that can apply to the bridge construction that we call it Bailey bridge system which can help the construction industry and the people especially when an emergency case. The country requires road and bridges which can cope with the increasing demands of growing internal and external commercial market. Bailey bridge system is one of the alternatives to solve the problems likes interm of time, installation and labors.